IMPLEMENTING DIFFERENTIATED INSTRUCTION THROUGH SHORT STORY READING AMONG THIRD GRADE STUDENTS AT SD NEGERI TANJUNGSARI - Nurhalijah, Neli; Helmanto, Fachri; Mawardini, Annissa (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
Enhancing reading literacy at the elementary level remains a critical challenge in foundational education, particularly in early-grade classrooms. This study examines the implementation of differentiated instruction through short story reading to develop the language skills of third-grade students at SD Negeri Tanjungsari. A descriptive qualitative approach was employed, with data gathered through classroom observation, interviews, and documentation. The findings reveal that differentiation strategies across process, content, and product dimensions effectively address students’ diverse needs, interests, and readiness levels. The intervention led to noticeable improvements in students’ intensive and creative reading abilities, including the strategic use of visual aids and dictionaries to comprehend texts. Key enablers included a calm classroom environment and engaging story content, while challenges were primarily related to text difficulty and external distractions. These findings suggest that differentiated instruction, when applied through short story reading, not only strengthens reading literacy but also fosters intrinsic motivation and peer interaction in language learning activities.